THE RISE OF NON-NATIVE ENGLISH ACCENTS - Karimjonovna Shakhlokhon Ravshanjonovna; Madaminova Durdonaxon Abduxakim qizi (TADQIQOTLAR, 2025)
Annotation. This article explores the rise of non-native English accents, examining the key factors behind their growing acceptance and prominence. It highlights the role of globalization, technological innovation, and the increasing diversification of media in shaping the spread of English across the world. Non-native English speakers are now more visible in global communication, with platforms such as social media, streaming services, and the widespread use of English in education and the workforce offering them an increasingly prominent stage. The article further explores how the traditional perceptions of "correct" English—once dominated by native accents from countries like the UK and the US— are being challenged. As the article points out, accents are deeply tied to cultural identity, and this growing acceptance of non-native accents reflects a shift towards embracing linguistic diversity. In academic and professional spheres, non-native accents are increasingly recognized as assets that contribute to global competency, cultural understanding, and inclusivity, rather than as limitations. This evolution represents a broader trend towards recognizing the value of linguistic diversity in a globally interconnected world